Monocytes in neonatal stroke and hypoxic‐ischemic encephalopathy: Pathophysiological mechanisms and therapeutic possibilities - Pedro M. Pimentel‐Coelho (Neuroprotection, 2023)
Abstract Neonatal arterial ischemic stroke (NAIS) and neonatal hypoxic‐ischemic encephalopathy (HIE) are common causes of neurological impairments in infants, for which treatment options are very limited. NAIS and HIE induce an innate immune response that involves the recruitment of peripheral immune cells, including monocytes, into the brain. Monocytes and monocyte‐derived cells have the potential to contribute to both harmful and beneficial pathophysiological processes, such as neuroinflammation and brain repair, but their roles in NAIS and HIE remain poorly understood. Furthermore, recent evidence indicates that monocyte‐derived macrophages can persist in the brain for several months following NAIS and HIE in mice, with possible long‐lasting consequences that are still unknown. This review provides a comprehensive overview of the mechanisms of monocyte infiltration and their potential functions in the ischemic brain, focusing on HIE and NAIS. Therapeutic strategies targeting monocytes and the possibility of using monocytes for cell‐based therapies are also discussed.